Trends in fixed income investing in bonds - Lydon, Tom, 1960-; Lydon, Tom, 1960-; Safari eBooks (Upper Saddle River, N.J. : Pearson Education publishing as FTPress Delivers, 2010)
"Understanding today's bond market-and using it to increase your returns while managing your risk. If you liked this Element, read more from Tom Lydon, including The ETF trend following playbook: profiting from trends in bull or bear markets with exchange traded funds (ISBN: 9780137029013)"--Resource description page.
Description based on resource description page (viewed Mar. 17, 2010).
"An e-burst of inspiration from the best books"--Cover.
Keywords: Bond market; Government securities; Municipal bonds -- Ratings and rankings; Investments -- Decision making; Electronic books